Water quality analysis of Lagoa do Japiim, Manaus - Amazonas (Research, Society and Development, 2024)
Several aquatic environments, including urban lagoons, are being eutrophicated due to human occupation and sewage disposal. Lagoa do Japiim, located in the city of Manaus-Amazonas, has been degraded for decades by human action. The objective of this study was to evaluate the water quality of Lagoa do Japiim through resolution N°357 of the National Environmental Council (CONAMA) of March 17, 2005. Parameters such as temperature, pH, conductivity, color, turbidity, dissolved oxygen, chloride, nitrate and sulfate were measured at the initial and final points of the lagoon. The values found for color, dissolved oxygen and sulfate analyzes did not comply the standard required by legislation for class 2 water bodies, with the sulfate anion being the one that showed the highest degree of anthropization. Furthermore, the results obtained at the initial and final points of the lagoon revealed that both are heavily polluted. Therefore, this study highlights the importance of monitoring the water quality of urban lagoons, as these changes can compromise both aquatic biodiversity and supervision, aquaculture, fishing and primary contact activities.